EFFECT OF POD RELATED TRAITS ON SHATTERING IN M3 MUTANTS OF MUNGBEAN ( ANTS OF MUNGBEAN (Vigna radiata igna radiata (L.)Wilczek) ilczek) - N. VAIRAM (The Bioscan, 2018)
Mutation was induced by physical mutagen and chemical mutagen, viz., Gamma rays and Ethyl Methane Sulphonate (EMS) in two mungbean genotypes viz., CO (Gg) 7 and NM 65 and M3 generation was raised at the research farm of Agricultural College and Research Institute, Madurai during Kharif season 2013. The objective of this study was to analyze the mean performance and association analysis of eight important pod related traits along with shattering percentage in the 22 mutants of M3 generation. Pod related characters viz., pod width, number of pods per plant, number of seeds per pod, hundred seed weight and single plant yield showed significant negative association with shattering percentage. Pod length, pod length: width ratio, pod width: length ratio, pods per plant and seeds per pod had direct effect on shattering percentage. The result revealed that nine mutants viz., M26, M44, M46, M58, M70, M71, M84, M92 and M98 showed tolerance to pod shattering in M3 generation.